The Prospect of Integrated Farming System of Crops-Fish-Husbandary as the Survival Strategy to Secure the Farmers’ Economy: Case Study in Magelang - Indonesia - Prajanti, Sucihatiningsih Dian Wisika; Susilowati, Indah (International Journal of Economics and Financial Issues, 2016)
Agriculture plays an important role in Indonesian economy with its share of 14.4% to the GDP per 2013. In facts, number of farmers nowadays is declining in line with decreasing in land-use for agriculture. All of this could brought about the decrease in productivity, particularly in the existence of climate change phenomena. The heavy peasant life need an alternative survival strategy. One of the survival strategy practiced by farmers is through integrated farming system for crops-fish-husbandary. This study is aimed to formulate the suvival strategy to secure the economy of household farmers through integrated farming system. Interviews with farmers, relevant parties/ stakeholders or informants were carried out. The approach of integrated farming system was employed in the study. It is found that integrated farming system of fish-crops-husbandary is significant to secure a their household economy. Farmer produces differentiated products based on market demand to ensure their sufficient montly income. Keywords: Farming; Survival; Strategy JEL Classifications: Q12; Q15; Q55